A prospective randomized phase II study comparing metronomic chemotherapy with chemotherapy (single agent cisplatin), in patients with metastatic, relapsed or inoperable squamous cell carcinoma of head and neck. Issue 3 (March 2015) - Patil, Vijay Maruti; Noronha, Vanita; Joshi, Amit; Muddu, Vamshi Krishna; Dhumal, Sachin; Bhosale, Bharatsingh; Arya, Supreeta; Juvekar, Shashikant; Banavali, Shripad; D'Cruz, Anil; Bhattacharjee, Atanu; Prabhash, Kumar
Abstract Background Cetuximab based treatment is the recommended chemotherapy for head and neck squamous cell cancers in the palliative setting. However, due to financial constraints, intravenous (IV) chemotherapy without cetuximab is commonly used in lesser developed countries. We believe that oral metronomic chemotherapy may be safer and more effective in this setting. Methods We conducted an open label, superiority, parallel design, randomized phase II trial comparing oral MCT [daily celecoxib (200 mg twice daily) and weekly methotrexate (15 mg/m2)] to intravenous single agent cisplatin (IP) (75 mg/m2) given 3 weekly. Eligible patients had head and neck cancers requiring palliative chemotherapy with ECOG PS 0–2 and adequate organ functions who could not afford cetuximab. The primary end point was progression-free survival. Results 110 Patients were recruited between July 2011 to May 2013, 57 randomized to the MCT arm and 53 to the IP arm. Patients in the MCT arm had significantly longer PFS (median 101 days, 95% CI: 58.2–143.7 days) compared to the IP arm (median 66 days, 95% CI; 55.8–76.1 days) (p = 0.014). The overall survival (OS) was also increased significantly in the MCT arm (median 249 days, 95% CI: 222.5–275.5 days) compared to the IP arm (median 152 days, 95% CI: 104.2–199.8 days) (p = 0.02). There were fewer grade 3/4 adverse effects with MCT, which was not significant. (18.9% vs. 31.4%, P = 0.14). Conclusion Oral metronomic chemotherapy has significantly better PFS and OS than single agent platinum in the palliative setting.